2013
DOI: 10.1002/jctb.4178
|View full text |Cite
|
Sign up to set email alerts
|

Improved production of poly(γ‐glutamic acid) by Bacillus subtilisRKY3 and its recovery from viscous fermentation broth as a biodegradable polymer

Abstract: BACKGROUND Physiological parameters (culture pH, aeration rate, and agitation speed) were optimized to improve γ‐PGA production by batch culture of Bacillus subtilis RKY3. The optimum conditions for recovery of γ‐PGA from highly viscous culture broth were also investigated. RESULTS Enhanced γ‐PGA production (41.4 g L−1, 397 cP) was observed under optimized physiological culture parameters (no pH control, 1.5 L min−1 aeration, and 300 rpm agitation). The cells were completely removed by diluting the viscous cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Yoon et al [23] achieved only 35 g/L of γ-PGA with 1g/L/h productivity using optimized fed-batch fermentation by Bacillus licheniformis. Jeong et al [24] and Zhang et al [9] also reported similar low production of γ-PGA using Bacillus subtilis RKY3 and an optimized fermentation process. Table 3.…”
Section: Fed-batch Fermentationmentioning
confidence: 85%
“…Yoon et al [23] achieved only 35 g/L of γ-PGA with 1g/L/h productivity using optimized fed-batch fermentation by Bacillus licheniformis. Jeong et al [24] and Zhang et al [9] also reported similar low production of γ-PGA using Bacillus subtilis RKY3 and an optimized fermentation process. Table 3.…”
Section: Fed-batch Fermentationmentioning
confidence: 85%
“…licheniformis CGMCC2876 contains an abundant amount of amino sugars (Xiong et al, ), and polysaccharides can also be used as carbon or nitrogen sources(Ferreira et al, ; Zhurina et al, ). Similarly, there are studies reporting that microorganisms secrete γ‐PGA depolymerase to degrade γ‐PGA as a nutrient source when the medium only contains γ ‐PGA (Jeong et al, ; Kunioka and Goto, ). Our research provides culture strategies for improving the production of biopolymeric flocculants by B .…”
Section: Discussionmentioning
confidence: 99%
“…The majority studies on γ‐PGA strains have been focused on wild‐type Bacillus species, such as B. subtilis IFO3335 (Goto and Kunioka, ), B. subtilis F‐2‐01 (Kubota et al ., ), B. subtilis NX‐2 (Xu et al ., ), B. subtilis ZJU‐7 (Shi et al ., ), B. subtilis RKY3 (Jeong et al ., ), B. licheniformis ATCC 9945a (Ko and Gross, ), B. licheniformis WX‐02 (Wei et al ., ) and B. amyloliquefaciens LL3 (Cao et al ., ), which produced γ‐PGA usually at the yields of more than 10 g l −1 . However, the yield of γ‐PGA still need to be further improved.…”
Section: Introductionmentioning
confidence: 99%